Deliberation on continuous spread of corruption in South Africa - Vyas-Doorgapersad, Shikha (Edelweiss Applied Science and Technology, 2024)
Corruption is widely spread in South Africa and is against the norms of honestly, morals, values, ethics, and good governance. The reasons of corruption may be individual (personal greed for luxury, power, authority), organisational (inadequate monitoring and evaluation, reporting processes), legislative (no compliance), strategic (lack of ethical culture), to state a few. The study is aimed to find answers to the following guiding research question, such as: what is the extent of corruption in South Africa? The qualitative study utilised secondary sources through the literature review of articles and document review of annual/official reports to gather relevant information. The information was further assessed using document analysis. The findings show that corruption is spreading at every level of government, and even public and private sectors are getting exposed to cases of misconduct. The country has established various legislative frameworks to combat corruption. The objectives of anti-corruption frameworks are operationalised through the establishment of anti-corruption organistaions. Some of them are Corruption Watch; National Anti-Corruption Advisory Council; Financial Intelligence Centre; Organisation Undoing Tax Abuse; and National Anti-Corruption Hotline. The findings show that although there are anti-corruption measures in place, the inadequate compliance may create implementation gaps, hence corruption keeps on spreading at political level, bureaucratic offices, and even in municipalities. The study suggests policy measures to minimise the scope and spread of corruption.